EFFECT OF PHOSPHATE SOLUBILIZERS AND FYM ON MICROBIAL POPULATION OF SOYBEAN FIELD [GLYCINE MAX (L.) MERRILL] - MEENA , SURESH; R. P. GHASOLIA (The Bioscan, 2013)
Soybean [Glycine max (L.) Merrill] is an all famous oil seed as well as pulse crop which contains 40-44 % protein, 20 % oil and many other nutrients. A field experiment was conducted to know the effect of phosphate solubilizing bacteria and fungi and FYM on microbial population of soybean field during Kharif season 2009-10. Among treatments, Aspergillus awamori and Bacillus polymixa were used as seed treatment @ 20 g/kg seed and phosphorus levels were given through SSP (50 and 25 % P2O5 ) and FYM levels (5 and 2.5 t/ha) as applied into the soil. Seed treatment with A. awamori increased fungal (25.25 and 29.06 cfu x 103/g) and actinomycetes population (23.44 and 26.19 cfu x 108/g) while B. polymixa increased phosphate solubilizing bacterial counts (21.37 and 23.31 cfu x 106/g) significantly at 30 and 60 DAS, respectively. Application of FYM (5 t/ha) had significantly increased the fungi (22.21 and 27.25 cfu x 103/g), actinomycetes (20.37 and 23.77 cfu x 108/g), bacterial (30.55 and 36.02 cfu x 106/g) and PSB population (18.42 and 21.30 cfu x 106/g) in the soybean field at 30 and 60 DAS, respectively. Thus, it can be concluded that the application of Aspergillus awamori (20 g/kg seed) and FYM (5 t/ha) are better to increase microbial population as well as yield attributes of soybean in the field.